Strategy and Implementation of Poverty Alleviation through New and Renewable Energy in East Sumba - Ramompas, Yuvensius; Thimotius, Reynaldi; Huru, Delvinyo Enrico Rede (Jurnal Mebis, 2025)
East Sumba Regency is located in East Nusa Tenggara (NTT) Province, Indonesia, a region known for its abundant natural resource potential, especially New and Renewable Energy (NRE) sources such as biomass, wind, and solar. The people of East Sumba Regency have long utilised NRE, as reflected in traditional concepts and practices, including the local wisdom of "Marapu". This potential and socio-cultural conditions encouraged the central and regional governments to develop NRE projects, referring to the "Asta Cita Pemerintah" concept through the national programme "Sumba Iconic Island" (SSI), with a target of achieving 100% energy availability from NRE by 2024. This study aims to identify, analyse, and implement poverty alleviation strategies through renewable energy management, while ensuring that local wisdom-based regulations can be implemented effectively. The data collection techniques employed are observation, documentation, and focus group discussions (FGDs). The analysis method employed was descriptive analysis, which involved describing the collected data using the PESTLE and SOAR approaches. The results of the study indicate that the most effective strategy for poverty alleviation through the management of new renewable energy (NRE) based on local wisdom in the East Sumba district is the S-A strategy.